Randomised controlled trials of mood stabilisers for people with autism spectrum disorder: systematic review and meta-analysis - Bharati Limbu; Shoumitro Deb; Meera Roy; Rachel Lee; Ashok Roy; Oluwafemi Taiwo (BJPsych Open, 2022)
Background Despite the widespread use of psychotropic medications in people with autism spectrum disorder (ASD), there is limited evidence to suggest that psychotropic medications including mood stabilisers are effective in individuals with ASD.